2017
DOI: 10.22610/jebs.v9i2(j).1660
|View full text |Cite
|
Sign up to set email alerts
|

E-Communication and Customer Satisfaction: a Case of the Mobile Telecommunications Industry in South Africa

Abstract: Electronic communication (e-communication) refers to communicating by electronic means, especially over computer networks. Organisations use the internet to distribute valuable content in a variety of ways including e-newsletters, articles, videos, webinars, chats, live online events, social networks and forums. Customer satisfaction measures how well the expectations of a customer concerning a product or service provided by an organisation have been met. Customers can be satisfied with more than just the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Based on some studies that used customer satisfaction as a variable [29][30][31][35][36][37][38][39][40][41][42][43][44][45][75][76][77] and exploring the behavioral intention of consumers and actual usage, we have introduced the variable consumers' satisfaction into the proposed conceptual model (TAM modified). Our research has shown that consumers' satisfaction significantly influences the extent of m-commerce use and future behavioral intention.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on some studies that used customer satisfaction as a variable [29][30][31][35][36][37][38][39][40][41][42][43][44][45][75][76][77] and exploring the behavioral intention of consumers and actual usage, we have introduced the variable consumers' satisfaction into the proposed conceptual model (TAM modified). Our research has shown that consumers' satisfaction significantly influences the extent of m-commerce use and future behavioral intention.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the need for further research due to uncertainties about some vectors that cause customers to engage in m-commerce, customer perceptions of the benefits offered by m-commerce, the post-purchase experience, and how benefits are perceived compared to other channels [30,[38][39][40][41][42][43]. Kalinic et al [40] and other researchers [43][44][45][46] believed that empirical studies are needed on the evolution of consumers' adoption of this channel and the factors influencing customers' attitudes in opting for m-commerce. All researchers who have studied the evolution of this channel agree that trade operators must consider m-commerce in order to understand that the lifestyle of customers and the increasingly advanced features of mobile devices can revolutionize the evolution of trade.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations